SGC stimulators: Evidence for riociguat beyond groups 1 and 4 pulmonary hypertension. (January 2017) - Benza, Raymond; Mathai, Stephen; Nathan, Steven D.
Abstract: Pulmonary hypertension (PH) is a chronic cardiopulmonary disorder that if left untreated, progresses rapidly and is ultimately fatal. The World Health Organization (WHO) has classified PH into 5 distinct groups according to pathophysiology, hemodynamic characteristics, and clinical presentation. Dysfunction in the nitric oxide (NO) pathway plays a key role in the pulmonary hypertension disease process, including in WHO Groups 2 and 3 PH. PH is associated with endothelial dysfunction, impaired synthesis of NO, and insufficient stimulation of the NO–soluble guanylate cyclase (sGC)–cyclic guanosine monophosphate (cGMP) pathway, which reduces cGMP production. cGMP regulates vascular tone, cellular proliferation, inflammation, and fibrosis and its depletion can lead to a variety of abnormalities, including pulmonary vasoconstriction, impaired vascular remodeling, and in situ thrombosis. This review will examine a novel class of drugs called sGC stimulators which directly stimulate sGC independently of NO, leading to increased production of cGMP. Highlights: Riociguat stimulates sGC independently of NO, increasing production of cGMP. Riociguat improved hemodynamics w/out interfering with gas exchange in PH-ILD. Riociguat's antifibrotic properties may be beneficial in PH-sLVD.